CRISIS, HAZARD, AND DISASTER MANAGEMENT: A STUDY OF REGULATORY FORMULATION AND INSTITUTIONAL COORDINATION - Wardhono, Dwi Tjahja K.; Muhardini, Retno; Shalehanti, Nadhia; Simatupang, Dian Puji Nugraha (Bank Indonesia, 2023)
Management crises, hazards, and disasters should be carried out with an integrated and patterned approach through the formulation of clear regulations and efficient coordination of disaster management institutions. Both will provide effective management in responding to crises, averting hazards, and managing disasters that have the potential to occur across various countries. In developed countries where regulations are well structured, using mitigation protocols, all parties have understood their duties, functions, and responsibilitiesin dealing with these risks. However, in countries where unstructured regulation is unstructured, there are complexities and multiple interpretations of regulations and there are intersections of institutional authority, which creates vulnerabilities in dealing with risk. This study concludes the importance of an integrated risk mitigation system, both in terms of rules and regulatory formulation as well as coordination of institutions in one container. In addition to these factors, economic, sociological, and demographic characteristics in a country are also structural conditions that determine the optimal implementation of regulations and institutional coordination.